2009
DOI: 10.1063/1.3257242
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of magnetic properties in Ni nanowire arrays

Abstract: The angular dependence of the remanence and coercivity of Ni nanowire arrays produced inside the pores of anodic alumina membranes has been studied. By comparing our analytical calculations with our measurements we conclude that the magnetization reversal in this array is driven by means of the nucleation and propagation of a transverse wall. A simple model based on an adapted StonerWohlfarth model is used to explain the angular dependence of the coercivity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 32 publications
(45 reference statements)
8
54
0
6
Order By: Relevance
“…Many groups have studied the size dependant magnetic properties of NWs [14][15][16]. For magnetic recording applications the NW diameter is desired as small as possible, while for other applications such as in microwave and magneto-optical devices the NW with large diameters are favorable [17,18]. Qin et al [15] and Han et al [14] have reported Ni NWs with large diameters and explored their angular dependent magnetic properties in detail.…”
Section: Introductionmentioning
confidence: 98%
“…Many groups have studied the size dependant magnetic properties of NWs [14][15][16]. For magnetic recording applications the NW diameter is desired as small as possible, while for other applications such as in microwave and magneto-optical devices the NW with large diameters are favorable [17,18]. Qin et al [15] and Han et al [14] have reported Ni NWs with large diameters and explored their angular dependent magnetic properties in detail.…”
Section: Introductionmentioning
confidence: 98%
“…5 shows a good agreement between the experimental results (dots) and theoretical calculations (line), performed using SðhÞ ¼ S 0 jcos hj, where S 0 ¼ Sðh ¼ 0 Þ. 15 To investigate the magnetization reversal processes of Co NW and NT arrays, we analyzed the angular dependence of H c . Previous works reported analytical calculations of the magnetic reversal modes [coherent (C) magnetization rotation, and transverse (T) and vortex-like (V) domain walls] that are energetically more favorable for high aspect ratio NWs and NTs.…”
Section: B Magnetization Reversalmentioning
confidence: 95%
“…Previous works reported analytical calculations of the magnetic reversal modes [coherent (C) magnetization rotation, and transverse (T) and vortex-like (V) domain walls] that are energetically more favorable for high aspect ratio NWs and NTs. 8,[13][14][15]20,27,[38][39][40] For analytical calculations it is important to define the parameter b ¼ d i =d, where d i and d are the NT inner and outer diameters, respectively, (Fig. 5).…”
Section: B Magnetization Reversalmentioning
confidence: 99%
See 1 more Smart Citation
“…En particular, resulta atractivo el estudio de sistemas nanométricos metálicos (como el Ni) debido a su pequeña anisotropía magneto-cristalina y potenciales aplicaciones en dispositivos magnéticos [9][10][11][12].…”
Section: Introductionunclassified